Makorin 1 is required for Drosophila oogenesis by regulating insulin/Tor signaling. - Eui Beom Jeong; Seong Su Jeong; Eunjoo Cho; Eun Young Kim (PLoS ONE, 2019)
Reproduction is a process that is extremely sensitive to changes in nutritional status. The nutritional control of oogenesis via insulin signaling has been reported; however, the mechanism underlying its sensitivity and tissue specificity has not been elucidated. Here, we determined that Drosophila Makorin RING finger protein 1 gene (Mkrn1) functions in the metabolic regulation of oogenesis. Mkrn1 was endogenously expressed at high levels in ovaries and Mkrn1 knockout resulted in female sterility. Mkrn1-null egg chambers were previtellogenic without egg production. FLP-FRT mosaic analysis revealed that Mkrn1 is essential in germline cells, but not follicle cells, for ovarian function. As well, AKT phosphorylation via insulin signaling was greatly reduced in the germline cells, but not the follicle cells, of the mutant clones in the ovaries. Furthermore, protein-rich diet elevated Mkrn1 protein levels, without increased mRNA levels. The p-AKT and p-S6K levels, downstream targets of insulin/Tor signaling, were significantly increased by a nutrient-rich diet in wild-type ovaries whereas those were low in Mkrn1exS compared to wild-type ovaries. Taken together, our results suggest that nutrient availability upregulates the Mkrn1 protein, which acts as a positive regulator of insulin signaling to confer sensitivity and tissue specificity in the ovaries for proper oogenesis based on nutritional status.